Simulated Annealing : Advances, Applications and Hybridizations - de Sales Guerra Tsuzuki, Marcos; de Sales Guerra Tsuzuki, Marcos (IntechOpen, 2012)
Simulated Annealing is a probabilistic meta-heuristic that is based on statistical mechanics: while at high temperatures molecules in a liquid move freely, the slow reduction of temperature decreases the thermal mobility of the molecules. The final state forms a pure crystal which also corresponds to a state of minimum energy. We encourage readers to explore SA in their work, mainly because it is simple and because it can yield very good results.
English
Keywords: Fluid mechanics; Dynamics & statics